2018
DOI: 10.1108/jd-07-2017-0101
|View full text |Cite
|
Sign up to set email alerts
|

Pragmatic thought as a philosophical foundation for collaborative tagging and the Semantic Web

Abstract: Purpose The purpose of this paper is to use ideas drawn from two founders of American pragmatism, William James and Charles Sanders Peirce, in order to propose a philosophical foundation that supports the value of collaborative tagging and reinforces the structure and goals of the Semantic Web. Design/methodology/approach The study employs a close analysis of key literature by James and Peirce to answer recent calls for a philosophy of the Web and to respond to research in the LIS literature that has assesse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…STs contain useful information about a user's choice of tagging objects, tagging perspective and tag presentation, which makes users choose to follow and imitate (Oliveira et al, 2008). It showed that the STs caused users to create tags that were semantically related (Bruhn and Syn, 2018). Cattuto et al (2007) proved that behind the fact of semantic relations, similar tagging behaviour was shared, although the differences did exist in a user's information goals and tag choices.…”
Section: Related Workmentioning
confidence: 99%
“…STs contain useful information about a user's choice of tagging objects, tagging perspective and tag presentation, which makes users choose to follow and imitate (Oliveira et al, 2008). It showed that the STs caused users to create tags that were semantically related (Bruhn and Syn, 2018). Cattuto et al (2007) proved that behind the fact of semantic relations, similar tagging behaviour was shared, although the differences did exist in a user's information goals and tag choices.…”
Section: Related Workmentioning
confidence: 99%
“…As PG falls into the category of unstructured image data, the annotation process (tagging) on scanned pages would be more a suitable option (Zeng, 2019). The annotation greatly assists in the discovery of information since tags represent the main concepts on each textual image (Bruhn and Syn, 2018; Featherston et al , 2019; Minsky, 1982). The tagging can be provided in the form of keywords, free text or by using a predefined set of terms, taxonomies or ontologies (Dasiopoulou et al , 2011).…”
Section: Related Workmentioning
confidence: 99%